COMPETENCY AESTHETIC AND SLIGHT OF THE PROPHETS - Osman MUTLUEL (Fırat University, 2019)
The concept of competence, next to the main branches, sub-Branching out is extremely important today, emerges as an important concept. Competence of different meanings according to each discipline, often in philosophy, in particular in terms of Islamic philosophy has become an extremely important concept. Especially what is human competence and competent people is extremely important which features should have won. In this respect, this study, the first human who is proficient in the philosophy of Islam? And these people have taken up what properties? The answer to the questions were put forward. At the same time, Focused on the relationship between the Prophet with competent human Also, the perfection criteria for the Prophet’s behaviors has been extracted. Accordingly; in addition to the physical characteristics of the Prophet, as like criteria that should be taken as an example of moral perfection; his sitting, eating, speech, modesty, joking, clothing, laughing, understanding of cleaning, contentment, to have full of trust with one he gave him a responsibility, devotion to the right and justice, forgiveness and compassion, to have a vision, risk-taking and determination are taken as an example of perfection for the people who believed in him. According to the Islamic philosophers, competent person, as well as being capable of thinking, must gather the moral virtues in himself. In addition, the more these features are found in a person, the more the degree of competence increases. So, the less they are found the less his perfection degree decreases.